Ambient Media and Systems Second International ICST Conference, AMBI-SYS 2011, Porto, Portugal, March 24-25, 2011, Revised Selected Papers - Gabrielli, Silvia; Elias, Dirk; Kahol, Kanav (Springer eBooks., 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the Second International ICST Conference on Ambient Systems and Media, AMBI-SYS 2011, held in Porto, Portugal in March 2011. The 10 revised full papers presented were carefully reviewed and selected and cover a wide range of topics as innovative solutions in the field of ambient assisted living, providing a new physical basis for ambient intelligence by also leveraging on contributions offered by interaction design methods and approaches.